A Case Report of Compound Odontoma Associated with an Unerupted Maxillary Central Incisor - Eda Arat Maden; Ceyhan Altun; Metin Sencimen (Archives of Clinical and Experimental Surgery, 2014)
Odontomas generally appear as small, solitary or multiple radio-opaque lesions found on routine radiographic examinations. Traditionally, odontomas are the most common type of odontogenic tumor and they are generally asymptomatic. Occasionally, odontomas may cause disturbances in the eruption of teeth, such as impaction, delay eruption or retention of primary teeth. In general, odontomas occur more often in the permanent dentition. This is a case report of a compound composite odontoma in an 8-year-old boy, which has resulted in failure of eruption of the permanent upper right central incisor while the contra-lateral tooth had erupted. [Arch Clin Exp Surg 2014; 3(1.000): 47-51]